Identification of the first-in-class dual inhibitors of human DNA topoisomerase IIα and indoleamine-2,3-dioxygenase 1 (IDO 1) with strong anticancer properties - Barbara Kaproń; Anita Płazińska; Wojciech Płaziński; Tomasz Plech (Taylor & Francis Group, 2023)
Molecular docking of a large set of thiosemicarbazide-based ligands resulted in obtaining compounds that inhibited both human DNA topoisomerase IIα and indoleamine-2,3-dioxygenase-1 (IDO1). To the best of our knowledge, these compounds are the first dual inhibitors targeting these two enzymes. As both of them participate in the anticancer response, the effect of the compounds on a panel of cancer cell lines was examined. Among the cell lines tested, lung cancer (A549) and melanoma (A375) cells were the most sensitive to compounds 1 (IC50=0.23 µg/ml), 2 (IC50=0.83 µg/ml) and 3 (IC50=0.25 µg/ml). The observed activity was even 90-fold higher than that of etoposide, with selectivity index values reaching 125. In-silico simulations showed that contact between 1-3 and human DNA topoisomerase II was maintained through aromatic moieties located at limiting edges of ligand molecules and intensive interactions of the thiosemicarbazide core with the DNA fragments present in the catalytic site of the enzyme.